Normative Reasons for Love, Part II. Issue 8 (August 2014) - Smuts, Aaron
Abstract Are there normative reasons for love? More specifically, is it possible to rationally justify love? Or can we at best provide explanations for why we love? In Part I of this entry, I discuss the nature of love, theories of emotion, and what it takes to justify an attitude. In Part II, I provide an overview of the various positions one might take on the rational justification of love. I focus on the debate between defenders of the no‐reasons view and the reasons view. Along the way, I discuss the significance of falling in love, the problem of trading up, and the notion of irreplaceability. I evaluate attempts to justify love based on the intrinsic and the relational properties of the beloved.